Symptoms-Based Network Intrusion Detection System - Qassim Q.S.; Jamil N.; Mahdi M.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Anomaly detection; Classification (of information); Computer crime; Engines; Intrusion detection; Network security; Anomaly; Centralised; Cyber-attacks; Defence mechanisms; Detection agents; Feature; Intrusion Detection Systems; Malicious activities; Network intrusion detection systems; Signature; Machine learning